Investigation of vitamin D deficiency in girls with growth and development variations—a single center study - Huang, Panwang; Zeng, Beilei; Ren, Feng; Zhou, Yuan; Li, Ye; Huang, Yinyin; Liu, Xingyu; Zhou, Jiaxiu; Ma, Yaping (Frontiers in Pediatrics, 2025)
PurposeTo understand the status of vitamin D deficiency in girls with growth and developmental variations, as well as the impact of COVID−19 on their vitamin D levels, and to provide reference for the prevention and treatment of vitamin D deficiency in children.MethodsA retrospective analysis was conducted on 1,345 instances of girls with growth and developmental variations who visited our pediatric endocrinology department and completed vitamin D detection. A total of 279 girls with complete data were included in this study. Among them, 246 girls were classified into four groups based on different growth and developmental variations: early puberty group, menarche group, obesity group, short stature group, and 33 healthy girls served as the control group. Besides, the girls were divided into pre-epidemic and post-epidemic groups by the occurrence of the COVID-19 epidemic. Vitamin D were measured in all girls. The 25(OH)D <20 ng/ml was used as the standard for vitamin D deficiency.ResultsThe levels of vitamin D in the early puberty group, menarche group, obesity group, short stature group, and control group were as follows: 20.23 ± 5.90 ng/ml, 17.85 ± 5.69 ng/ml, 21.31 ± 8.99 ng/ml, 27.90 ± 12.27 ng/ml, and 29.42 ± 12.65 ng/ml, respectively. The levels of vitamin D in the early puberty group, menarche group, and obesity group were significantly lower than those in the control group (P < 0.05). The individual vitamin D deficiency rates in the aforementioned groups were 52.07%, 73.91%, 59.46%, 30.95%, and 30.30%, respectively. The vitamin D levels in the pre-epidemic and post-epidemic groups were 20.48 ± 6.22 ng/ml and 22.50 ± 9.74 ng/ml, respectively (P > 0.05).ConclusionGirls with early puberty, menarche, and obesity have a certain deficiency of vitamin D levels, and appropriate vitamin D treatment should be provided clinically. Girls with short stature and healthy girls also have certain levels of vitamin D deficiency, and awareness of prevention should be strengthened.